Advances in the Biosynthetic Pathways and Application Potential of Plasmalogens in Medicine - Zhou, Yulong; Yu, Ning; Zhao, Jie; Xie, Zhenming; Yang, Zhaonan; Tian, Bing (Frontiers in Cell and Developmental Biology, 2020)
Plasmalogens are a special class of polar glycerolipids containing a vinyl-ether bond and an ester bond at sn-1 and sn-2 positions of the glycerol backbone, respectively. In animals, impaired biosynthesis and regulation of plasmalogens may lead to certain neurological and metabolic diseases. Plasmalogens deficiency was proposed to be strongly associated with neurodegenerative and metabolic diseases, such as Alzheimer's disease and Parkinson’s disease, and appropriate supplement of plasmalogens could help to prevent and possibly provide therapy of these diseases. Plasmalogens evolved first in anaerobic bacteria with an anaerobic biosynthetic pathway. Later, an oxygen-dependent biosynthesis of plasmalogens appeared in animal cells. This review summarizes and updates current knowledge of anaerobic and aerobic pathways of plasmalogens biosynthesis, including the enzymes involved, steps and aspects of the regulation of these processes. Strategies for increasing the expression of plasmalogen synthetic genes using synthetic biology techniques under specific conditions are discussed. Deep understanding of plasmalogens biosynthesis will provide the bases for the use of plasmalogens and their precursors as potential therapeutic regimens for age-related degenerative and metabolic diseases.